GE_GERICHTE C/28032/2009 vom 17. Dezember 2013 - GE Cour de justice (2013)
DIVORCE; ENFANT; OBLIGATION D'ENTRETIEN; LIQUIDATION DU RÉGIME MATRIMONIAL; SÉPARATION DE BIENS; COPROPRIÉTÉ | CPC.311.1; CC.649; CC.650.1; CC.651.1; CC.251; CC.276; CC.285.1